2022
DOI: 10.3389/fmars.2022.1049056
|View full text |Cite
|
Sign up to set email alerts
|

Using geostatistical analysis for simultaneous estimation of isoscapes and ontogenetic shifts in isotope ratios of highly migratory marine fish

Abstract: Tracking migration of highly migratory marine fish using isotope analysis (iso-logging) has become a promising tool in recent years. However, application of this method is often hampered by the lack of essential information such as spatial variations in isotope ratios across habitats (isoscapes) and ontogenetic shifts of isotope ratios of target animals. Here, we test the utility of geostatistical analysis to generate isoscapes of δ13C and δ15N in the western Pacific and estimate the ontogenetic shifts in δ13C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The simulated d 15 N Nitrate values (Figure 3A) are annual mean surface values, whereas the observed values (Figure 3D) are the shallowest data that were measured in a single expedition compiled by and Fripiat et al (2021). The simulated d 15 N Phytplankton values (Figure 3B) are the weighted averages of the euphotic layer throughout the year, whereas the observed values (Figure 3E) are the d 15 N Base values estimated from the d 15 N measurements of bulk nitrogen and amino acids of zooplankton obtained from various depths and seasons (Matsubayashi et al, 2022). The simulated d 15 N PON values (Figure 3C) are the weighted averages of the euphotic layer throughout the year, whereas the observed values (Figure 3F) are the d 15 N Bulk values of surface sediments obtained from various depths and redox conditions compiled by NICOPP (Tesdal et al, 2013), which could be affected by digenesis.…”
Section: Horizontal Distributions Of Nitrate and Chlorophyll A Concen...mentioning
confidence: 93%
See 1 more Smart Citation
“…The simulated d 15 N Nitrate values (Figure 3A) are annual mean surface values, whereas the observed values (Figure 3D) are the shallowest data that were measured in a single expedition compiled by and Fripiat et al (2021). The simulated d 15 N Phytplankton values (Figure 3B) are the weighted averages of the euphotic layer throughout the year, whereas the observed values (Figure 3E) are the d 15 N Base values estimated from the d 15 N measurements of bulk nitrogen and amino acids of zooplankton obtained from various depths and seasons (Matsubayashi et al, 2022). The simulated d 15 N PON values (Figure 3C) are the weighted averages of the euphotic layer throughout the year, whereas the observed values (Figure 3F) are the d 15 N Bulk values of surface sediments obtained from various depths and redox conditions compiled by NICOPP (Tesdal et al, 2013), which could be affected by digenesis.…”
Section: Horizontal Distributions Of Nitrate and Chlorophyll A Concen...mentioning
confidence: 93%
“…The isotopic composition of animal tissues and local environments can be used as a natural tag to track an animal's movements through isotopically distinct habitats, called iso-logging (Matsubayashi et al, 2022). Nitrogen isotope (d 15 N) analysis of incremental growth tissues, such as eye lenses and vertebral bones, has proven promising for reconstructing migration routes and feeding environments over the animal's life (Matsubayashi et al, 2017;Harada et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is theoretically possible that the behavior observed in this individual reflects the ecology of ALB as a species rather than a characteristic unique to the individual. Promising future research direction to overcome the limitation of tagging studies (i.e., data quantity issue) involves using otolith trace element analysis (Macdonald et al, 2013) and Iso-logging (Matsubayashi et al, 2022), to estimate the track of movement simply by collecting substantial biological tissues. Unlike tagging research, these methods are not affected by the recapture rates and therefore could be a useful approach (Macdonald et al, 2013;Matsubayashi et al, 2022) to evaluate the migration in a more quantitative manner.…”
Section: Limitations and Assumptions Of This Studymentioning
confidence: 99%
“…Recent isotopic studies have demonstrated the potential of animal eye lenses for retrospective isotope analyses (Bell-Tilcock et al, 2021; Matsubayashi et al, 2022; Wallace et al, 2014). Eye lenses, primarily composed of structural proteins called crystallins, grow incrementally, and new tissues are sequentially added to the outermost part throughout an individual’s lifetime (Peebles & Hollander, 2020; Wride, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Once these tissues are formed, protein synthesis ceases, and they no longer experience metabolic turnover (Peebles & Hollander, 2020). Thus, longitudinal tissue segregation and isotope analysis of eye lenses can enable the reconstruction of individual behavioural histories from isotopic chronology (Bell-Tilcock et al, 2021; Matsubayashi et al, 2022; Peebles & Hollander, 2020). This method has successfully been applied in fish and cephalopods (Hunsicker et al, 2010; Wallace et al, 2014); however, its applicability and appropriate lens segregation methods in mammals have not yet been tested.…”
Section: Introductionmentioning
confidence: 99%